Lexikon zur Kernenergie. Ausgabe Januar 2017 - Koelzer, Winfried (KIT Scientific Publishing, 2017)
The scope of the Glossary of Nuclear Terms (Lexikon zur Kernenergie) is intended to focus on the key terms concerning the public debate about the peaceful use of nuclear energy, in order to explain the meanings of technical terms that may be unfamiliar to many people.